The Development 0f The Village Economic Potential Through Local Wisdom - Suryadi Suryadi; Nursahidin Nursahidin; Yusmanto Yusmanto; Reza Gusmanti (Universitas Negeri Padang, 2023)
As a tourist village, the Paledah Village area in Padaherang District, Pangandaran Regency, has potential that can be developed. This is because Paledah Village possesses many interesting characteristics. These characteristics include a unique social and cultural life and elements from nature which are pretty interesting. This research then aims to see and find out how the development of a tourist village that uses a base in the form of local wisdom. The data in this study came from various previous studies and studies that are still related to this research. This study found that the use of local wisdom was used in developing tourist villages. This can be seen in how organizational principles are implemented. The organizational principles include voluntary and open nature, democratic management, and independence. Meanwhile, there are five criteria for tourist villages, whereas Paladeh village has just two criteria already maximal, namely tourist attraction and empowerment. The other three criteria, namely accessibility, public facilities, and village facilities, are still not running optimally.